Toona Sinensis ameliorates insulin resistance via AMPK and PPARγ pathways1. Issue 6 (10th June 2015) - Liu, Hung-Wen; Huang, Wen-Cheng; Yu, Wen-Jen; Chang, Sue-Joan
<x xml:space="preserve">Abstract</x> Toona sinensis improves insulin sensitivity in high-fat-fed mice and directly stimulates glucose uptake via AMPKα in C2C12 myotubes.